Dermatological manifestations in cardiofaciocutaneous syndrome. (2nd January 2019) - Bessis, D.; Morice‐Picard, F.; Bourrat, E.; Abadie, C.; Aouinti, S.; Baumann, C.; Best, M.; Bursztejn, A.‐C.; Capri, Y.; Chiaverini, C.; Coubes, C.; Giuliano, F.; et al.
Summary: Cardiofaciocutaneous syndrome (CFC) is one of a group of rare genetic disorders called the RASopathies because they are caused by mutations in the genes related to HRAS, KRAS or NRAS . The other RASopathies are Noonan (NS) and Costello (CS) syndromes. These conditions can affect the heart, nervous system, bony skeleton and muscles; there is sometimes an unusual facial appearance and occasionally a tendency to develop tumours. CFC patients often have skin problems but dermatologists have difficulty recognising the syndrome because it is very rare and the skin symptoms are not particularly unusual. Also there is a lot of overlap between the different RASopathies. In this study from France, geneticists and dermatologists reviewed 45 patients with CFC caused by mutations in the genes BRAF, MAP2K1 or MAP2K2 and compared the findings with published data. They noted a lack of precise dermatological descriptions in the RASopathy literature. They observed certain skin conditions more frequently in CFC patients than is reported in the general population. These included common disorders such as prominent follicles (keratosis pilaris), multiple moles, and curly hair, and unusual but rather non‐specific features such as lax skin, thickened palms and soles, sparse eyebrows and excessive sweating. The thickened palms and soles responded well to treatment with a drug called acitretin in two patients. As the accompanying commentary points out, most people with these skin features do not have a RASopathy, but that diagnosis is worth considering if the skin condition is unusually marked, is absent in close family members, or associated with other abnormalities. Abstract : Linked Article:  Bessis et al. Br J Dermatol 2019;180 :172–180